Use of medicinal plants related to events of the female reproductive cycle in the county of Oliveira dos Campinhos, Santo Amaro, Bahia - Costa Neto, Eraldo M.; Santos, Liliane M.; Santos, Sofia Aline S.; Magalhães, Suzana F.; Amorim, Tatiane C. (SITIENTIBUS série Ciências Biológicas, 2005)
This article deals with the local usage of 16 plant ethnospecies related to woman’s health in the county of Oliveira dos Campinhos, Santo Amaro, Bahia State, Brazil. Both the use of plants linked to the female reproductive cycle and the childcare practices are discussed.